Curricula for teaching children and young people with severe or profound and multiple learning difficulties practical strategies for educational professionals - Imray, Peter; Hinchcliffe, Viv (David Fulton/NASEN, 2014)
"Curricula for Teaching Children and Young People with Severe or Profound and Multiple Learning Difficulties offers a range of compelling arguments for a distinct and separate pedagogical approach to the learning needs of the most educationally challenging pupils. This book, written in accessible, common sense and non-academic language, provides an easy-to-follow alternative curriculum specifically designed to enhance and enrich the learning of children with profound and multiple learning difficulties. Chapter by chapter, guidelines and support are offered in key curriculum areas, some of which include: - Cognition - Language, Literacy and Communication - Mathematical - Physical - Sensory - Creative - Care - Play - Problem solving. This highly practical resource is essential reading for any educational professional, parents, school governors, teachers, teaching assistants, therapists and indeed anyone involved with maximising the educational opportunities of those with profound learning difficulties. Peter Imray has been a teacher of children, young people and adults with special educational needs since 1986, mostly at The Bridge School in Islington, North London. He has combined his teaching role with forming and running the Bridge School's Training and Consultancy Centre, which has established itself as one of the UK's major trainers of those working with pupils and students with SLD, PMLD and ASD. Viv Hinchcliffe is Head of ASD services in Lewisham, and has national standing as an expert in special education"--Provided by publisher.